STRATEGI PENGENALAN ECO-ENZYME DAN PRODUK TURUNANNYA UNTUK MENINGKATKAN PENGETAHUAN MASYARAKAT MELALUI PAMERAN AKADEMIK HAJATAN BETAWI DI JATIWARINGIN, PONDOK GEDE - Qurrota Aýun; Isnain Ardiani; Karina Sheilla Nazua; Adelia Fitri; Rafidho Rafidho; Muhammad Syeka Danuarta (Jurnal Hilirisasi IPTEKS, 2024)
The aim of this activity is to introduce Eco-enzyme and its derivative products to the public through the Hajatan Betawi academic exhibition with the hope of increasing public awareness and knowledge about the benefits of Eco-enzymes especially of environmental sustainability. The subjects are visitors who come to the exhibition. The method used is PAR. Eco-enzyme has been prepared 3 months in advance to be used as a base material for making solid soap, dish soap and liquid fertilizer. The method is divided into four stages: planning, preparation, observation and implementation. Two strategies were carried out, namely offering products in front of the exhibition stand and going around. Based on the results, more and more people are familiar with Eco-enzyme and the benefits of its derivative products. Several visitors who are interested in looking around and asking questions about Eco-enzyme products. The results of this activity showed an increase in knowledge and interest in Eco-enzyme and its derivative products. Many visitors expressed interest in trying to make their own Eco-enzyme at home and applying its derivative products. Academic exhibitions like this are very effective in raising public awareness of the environment. The interactive and educational approach proved to be able to attract interest and provide a deeper understanding. The conclusion through academic exhibitions can open the insights of exhibition visitors to produce similar products based on the fermentation process of easily degradable organic materials. It is hoped that similar activities can continue to be carried out to support environmental conservation.